Review: Metode Peningkatan Kecepatan Disolusi Dikombinasi Dengan Penambahan Surfaktan: Review: The Different Methods of Enhancing Dissolution Rate by the Present of Surfactant - Sagala, Reynelda Juliani (Universitas Tadulako, 2019)
Dissolution and solubility rates are very important parameters in designing a pharmaceutical dosage form, especially for oral drug administration. Oral drugs that have low dissolution rates often require high doses loading to improve the absorption and effectiveness in order to achieve therapeutic concentration. The increasing of drug dose is a less safe alternative solution, therefore researchers have developed physics, chemistry, and other modification in order to increase dissolution rate. These methods such as salt formation, prodrug formation, particle size reduction (micro-crystallization), co-grinding, crystal modification, micellar solubilization and complex formation, solid dispersion and self emulsifying. This review paper will focus on different methods that will be compared with the present of surfactant in these methods. The present of surfactants was able to overcome the limitation of each methods with a mechanism for reducing surface tension, micellar formation, reducing contact angle and increasing of wetting behaviour. Therefore, the present of surfactant in modification of drug dosage form could be considered to increase dissolution rate in order to achieve therapeutic effect.